PUBLIC POLICIES TO PROTECT POPULAR AND SOLIDARITY ECONOMY ORGANIZATIONS IN ECUADOR - Caiza Ibarra, Ronnal (2023)
In Ecuador, the popular and solidarity economy system seeks to dynamize the country's economicsovereignty, strengthening and encouraging the actors of the system so that they can carry outprocesses of production, distribution and commercialization of goods and services of these actors.In effect, the qualitative foundations, based on the exegetical methods, documentary analysis andbibliographic review used allowed determining that, in order to achieve the goals pursued by thepopular and solidarity economy system, public policies connote importance and transcendencewithin the economic sovereignty and its system, since they encourage, make effective, promoteand encourage to fulfill the goals pursued by these organizations of the Popular and SolidarityEconomy system, consequently, the strengthening of the country's economic sovereignty.